Implementation of JIT: focusing on Matsushita Electronic Device (M) Sdn Bhd (MEDEM) / Zaiton Mohd Napiah - Mohd Napiah, Zaiton (1996)
Introduction of this report is based on the assesment of an effectiveness and difficulties of JIT techniques face by Matsushita Electronic Devices (M) Sdn Bhd in Shah Alam which cover Purchasing and Production Department. The company is a Japanese company who produce microchip component locally and oversea. The implementation of JIT manufacturing techniques have been written and discussed by several accounting experts. The slow acceptance of .TIT have caused manufacturers to lost their competitiveness. Most of the techniques involved changes in the factory operations, relationships with suppliers and workers. The aims of the JIT are to produce the required items at the required quantity and qualities at the precise time. This mean that the company manufacture just enough to meet the market demand. JIT always stress on the elimination of waste, good quality product and on time delivery. JIT always target for on time delivery service to their customer. Therefore any problem ocurred in the production should be eliminated to ensure that the products are produced smoothly and achieve the target on time. The employees participation and suppliers involvement are very important in order to achieve the company target. The paper focus mainly on the effectiveness and difficulties ocurred in Matsushita Electronic Device (M) Sdn Bhd. Since JIT always focus on elimination of waste, good quality product and on time delivery services, this paper will discuss in detail how these situation managed by the management of Matsushita which could lead better productivity and who are involved in implementing JIT system in this company.